Value of Swimming in Cardiac Rehabilitation and Internal Medicine - De Meirleir, K. (Biomechanics and Medicine in Swimming, 1983)
Our present society became conscious of the medical aspects of sports with the emerging emphasis on sports medicine and the whole area of adapted physical education. Surveys indicate that at least half of the population in most Western countries participate in one or more sports activities (Lambert et al., 1982). These primarily include walking, jogging, bicycling, swimming, tennis and team sports. Considerable publicity has been given to injuries and deaths of athletes, and discussions have centered on prevention and treatment of such accidents. Maintaining a good body form and functional capacity as well as concern for increasing the active lifespan have stimulated an interest in the role of endurance exercise for protecting the cardiovascular system. As a consequence of this increased enthusiasm at all levels of the population to become involved in some kind of physical activity, the internist is confronted with two main questions: (1) What is the role of physical activity in the prevention and therapy of medical illness? (2) How does one define contraindications to physical activity in certain instances? These questions are not easily answered since most physicians have not learned how to prescribe exercise. To my knowledge sports medicine is not included in most medical school curricula. Most of this article will be devoted to the role and the problems of exercise in cardiac rehabilitation with special emphasis on swimming as an endurance sport. Swimming for prevention and treatment of some medical disorders is reviewed briefly.